Antibacterial and antioxidant phlorizin-loaded nanofiber film effectively promotes the healing of burn wounds - Yang, Ying; Ma, Shuang; Li, Anning; Xia, Guofeng; Li, Min; Ding, Chuanbo; Sun, Xiaofei; Yan, Li; Yang, Min; Zhao, Ting (Frontiers in Bioengineering and Biotechnology, 2024)
Burns usually result in damage and loss of skin forming irregular wound wounds.The lack of skin tissue protection makes the wound site highly vulnerable to bacterial infections, hindering the healing process. However, commonly used wound dressings do not readily provide complete coverage of irregular wounds compared to regular wounds. Therefore, there is an urgent need to prepare a wound dressing with high antimicrobial efficacy for the administration of drugs to irregular wounds. In this study, a chitosan (CS)/polyvinylpyrrolidone (PVP) composite nanofiber membrane (CS/PVP/Phlorizin) loaded with root bark glycosides (Phlorizin) was developed using an electrostatic spinning technique. The incorporation of phlorizin, a natural antioxidant, into the fiber membranes notably boosted their antimicrobial and antioxidant capabilities, along with demonstrating excellent hydrophilic characteristics. In vitro cellular experiments showed that CS/PVP/ Phlorizin increased Hacat cell viability with the presence of better cytocompatibility. In scald wound healing experiments, Phlorizin-loaded nanofibrous membranes significantly promoted re-epithelialization and angiogenesis at the wound site, and reduced the inflammatory response at the wound site. Therefore, the above results indicate that this nanofiber membrane is expected to be an ideal dressing for burn wounds.